Screen Hustles, Grifts and Stings - Sargeant, Amy.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2016)
Screen Hustles, Grifts and Stings identifies recurrent themes and techniques of the con film, suggests precedents in literature and discusses the perennial appeal of the con man for readers and viewers alike. Core studies span from film (Catch Me If You Can, Paper Moon, House of Games) to television (Hustle), from Noir (The Grifters) to Romantic Comedy (Gambit). Frequently, the execution of the con is only finely distinguishable from the conduct of a legitimate profession and, challengingly, a mark is often shown to be culpable in his or her undoing. The best con films, it is suggested, invite re-watching and reward the viewer accordingly: who is complicit and when? How and where is the con achieved? When is the viewer party to the con? And what, if any, moral is to be drawn?
Keywords: Communication; Motion pictures-United States; Film genres